And Yet It Quakes! (Nietzsche and Voltaire). Issue 1 (March 2021) - Kofman, Sarah
Abstract : One of a handful of texts written by Sarah Kofman in the interim between the publication of her Explosion (1992, 1993), a 700-page analysis of Ecce Homo, and her sudden death in 1994, 'And Yet It Quakes!' is an unflinching contribution to her perennial analysis of Nietzsche's legacy. The essay opens with a presentation of the responses of Voltaire and Nietzsche to natural catastrophe: an earthquake in Lisbon in the case of the former, an earthquake in Ischia for the latter. Drawing on a metaphoric architecture of quaking or shakenness to draw together a variety of themes and problematics, the essay elaborates a rich comparative study of these two thinkers on the basis of their hasty passing-on from the '"humanitarian" considerations' which such catastrophes might evoke. After analysing the influence of Voltaire on Nietzsche and the rich synergies between the two, with particular reference to irony and laughter, to aristocratism, and to the function of a polemical hostility to Rousseau within their various projects, Kofman's essay closes with a complex — and somewhat ambivalent — affirmation of the radicality of the Nietzschean project. (This text, first published in Furor shortly before Kofman's death, is collected in the posthumous Imposture de la beauté et autres textes (Galilée, 1995) and in Tributs à Voltaire (Furor, 2017). The ayant-droit is favourable to publication.)